2012
DOI: 10.1155/2012/196264
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Production byAspergillus terreusUsing Agro-Biomass as Substrate in Solid State Fermentation

Abstract: Ability of two strains of Aspergillus terreus (ATCC 74135 and ATCC 20542) for production of lovastatin in solid state fermentation (SSF) using rice straw (RS) and oil palm frond (OPF) was investigated. Results showed that RS is a better substrate for production of lovastatin in SSF. Maximum production of lovastatin has been obtained using A. terreus ATCC 74135 and RS as substrate without additional nitrogen source (157.07 mg/kg dry matter (DM)). Although additional nitrogen source has no benefit effect on enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Lovastatin production was increased from 76 to 304mg/gds when particle size decreased from 2.0 to 0.4 mm. As reported by Jahromi et al [38], there are two different effects of particle size on SSF process at any given moisture content. The first is that smaller particle size increases the surface region of solid materials for the attachment and growth of the fungi; the second is that smaller particle size decreases inter-space between particles and gas phase oxygen transfer.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Lovastatin production was increased from 76 to 304mg/gds when particle size decreased from 2.0 to 0.4 mm. As reported by Jahromi et al [38], there are two different effects of particle size on SSF process at any given moisture content. The first is that smaller particle size increases the surface region of solid materials for the attachment and growth of the fungi; the second is that smaller particle size decreases inter-space between particles and gas phase oxygen transfer.…”
Section: Resultsmentioning
confidence: 74%
“…Manzoni and Rollini [37] statedthat by adjusting pH and gradually adding the carbon source, lovastatin productivity by filamentous fungi could improve fivefold. On the other hand, Jahromi et al [38] indicated that the initial pH element has no significant effect on lovastatin yield, because they found no significant alteration in lovastatin yield by A. terreus ATCC 20542 and A. terreus ATCC 74135 at pH of 5 to 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NMR analysis of standard was not shown. Since the hydroxyl form of lovastatin is not stable, lactone form is normally the primary lovastatin detected in the fermented products (Jahromi et al 2012 Figure S3(A),(B)). The chemical shifts are summarised in Table S1.…”
Section: Resultsmentioning
confidence: 99%